2006
DOI: 10.1002/dc.20409
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary well-differentiated fetal adenocarcinoma diagnosed by bronchial brush and immunocytochemistry

Abstract: A 41-yr-old man with a long history of cigarette smoking presented to his family physician with an intermittent cough of 4-wk duration. Physical examination revealed no remarkable findings. A chest roentgenogram showed a 3-cm mass lesion located near the hilum of his right lung. A chest CT-scan confirmed the lesion to be a well-demarcated and solid tumor located in the lobar bronchus of the right middle lobe. No hilar lymphadenopathy was identified. The patient underwent a bronchoscopy, and a tumor involving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…9,18-21 Additionally, there has been noted, in some studies, a focal tigroid background commonly identified at the edge of cellular aggregates. 9,[18][19][20][21] The findings in this case were in agreement with previous reports with respect to the identification of two distinct populations of cells in the presence of abundant stroma. These similar findings can also be suggestive of hamartoma or pleomorphic adenoma, however, this case, did not have the typical epithelial morphology of these latter two diagnoses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…9,18-21 Additionally, there has been noted, in some studies, a focal tigroid background commonly identified at the edge of cellular aggregates. 9,[18][19][20][21] The findings in this case were in agreement with previous reports with respect to the identification of two distinct populations of cells in the presence of abundant stroma. These similar findings can also be suggestive of hamartoma or pleomorphic adenoma, however, this case, did not have the typical epithelial morphology of these latter two diagnoses.…”
Section: Discussionsupporting
confidence: 92%
“…The cytomorphologic features of WDFA have been reported in a limited number of reports and have shown the presence of a dual population of cells: (1) small cells, uniform in appearance with inconspicuous nucleoli, prominent subnuclear vacuoles and less often supranuclear vacuoles that show an acinar and glandular architecture and (2) larger squamoid cells with prominent nucleoli, dense cytoplasm with morule formation . Additionally, there has been noted, in some studies, a focal tigroid background commonly identified at the edge of cellular aggregates …”
Section: Discussionmentioning
confidence: 99%
“…The mean age of patients is in the fourth decade, which is younger than conventional pulmonary adenocarcinoma 1 . Reports of the cytology of FA are very rare, with only six cases of well‐differentiated FA being previously reported in the English literature 1–5 . Therefore, the present case is the first reported example of cytological findings of FA with a poorly differentiated component.…”
mentioning
confidence: 68%
“…Although most of FAs are well‐differentiated, a variant designated poorly differentiated FA has been described 6 . A literature review identified six reported cases of well‐differentiated FA sampled by fine needle aspiration or bronchial brushing 1–5 . In these reported cases, smears were composed of clusters arranged in irregular sheets or three‐dimensional structures.…”
mentioning
confidence: 99%
“…The cytological features of LGFA have rarely been described. A literature review identified 10 reported cases of LGFA sampled by fine needle aspiration or bronchial brushing 9–16 . Table 1 summarizes the clinicopathologic characteristics, cytologic specimen types, and preparation methods of these reported cases and the current case presented in this report 9–16 .…”
Section: Discussionmentioning
confidence: 99%